Money upside down a paradigm shift in economics and monetary theory? - Haas, Harald (Central banking, financial markets and monetary unions, 2004)
"A historic analysis of the evolution of money and credit reveals how the nature of money changed: private property plus interest, tally sticks, coinage, fractional reserve banking, gold standards, fiat currencies, debasement of fiat against gold." "The results of the historic analysis are combined with the new theories of money, credit, and finance of Bethmann, Heinsohn, Kindleberger, Kutyn, Malik, Martin, Minsky, Nuri, Rothbard, Soddy, Soros, and Steiger." "Their integration forms a stringent economic theory that is able to explain the past and present economic and financial system from a very new perspective executing a paradigm shift in economics, finance, and monetary theory."--Jacket.